2008
DOI: 10.3354/meps07363
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar genetic population structure of capelin Mallotus villosus

Abstract: Capelin Mallotus villosus is the most abundant pelagic fish species in boreal and subarctic waters. The ecological and commercial importance of capelin emphasizes the need for a better understanding of the genetic population structure of the species and the mechanisms underlying its population dynamics. With this aim, 1155 capelin from the entire distributional range of the species were genotyped using 9 recently-developed microsatellite markers. The genetic analyses clearly demonstrated that the circumpolar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…The presence of a CO1 sequence from Davis Strait in the same clade as those from the Chukchi and Bering Seas supports Dodson et al's (2007) hypothesized distribution pattern for the Arctic clade, from the Bering Sea to the Labrador Sea via the Beaufort Sea and Canadian Arctic. The microsatellite study by Praebel et al (2008) showed complementary fine-scale structuring of M. villosus but did not include samples from within the greater portion of the geographic range of Dodson et al's (2007) Arctic clade.…”
Section: Osmeridae (Smelts)mentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of a CO1 sequence from Davis Strait in the same clade as those from the Chukchi and Bering Seas supports Dodson et al's (2007) hypothesized distribution pattern for the Arctic clade, from the Bering Sea to the Labrador Sea via the Beaufort Sea and Canadian Arctic. The microsatellite study by Praebel et al (2008) showed complementary fine-scale structuring of M. villosus but did not include samples from within the greater portion of the geographic range of Dodson et al's (2007) Arctic clade.…”
Section: Osmeridae (Smelts)mentioning
confidence: 96%
“…Recently, several lines of evidence have been applied in analyses of capelin relationships (e.g., Stergiou 1989;Dodson et al 2007;Praebel et al 2008;Skurikhina et al 2010). Four highly divergent mitochondrial-DNA (mtDNA) clades were revealed in M. villosus from the North Atlantic, North Pacific, and Arctic Oceans by Dodson et al's (2007) analysis.…”
Section: Osmeridae (Smelts)mentioning
confidence: 99%
“…Capelin spend most of their life feeding in offshore waters; at maturation, they undergo extensive inshore migrations to spawning grounds at either beach or demersal (at depths of up to 90 m) sites (Carscadden and Nakashima 1997). Previous genetic studies concluded that capelin in the north Atlantic are subdivided into two distinct clades: the northwest Atlantic (Newfoundland, St. Lawrence Estuary, and Hudson's Bay) and the northeast Atlantic (Iceland and Barents Sea) (e.g., Dodson et al 2007;Praebel et al 2008;Colbeck et al 2011). These geographically delineated clades show differences in vertebral number, fecundity, egg size, and spawning mode (Stergiou 1989).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to cod and herring (for which there are at least 20-50 published genetic studies on a variety of spatial scales; Reiss et al 2009), fewer than 10 population genetic studies have been conducted on capelin in the north Atlantic. The majority of these investigations have been on scales spanning their north Atlantic distribution (e.g., Praebel et al 2008;Colbeck et al 2011) or using mitochondrial DNA (mtDNA) markers (e.g., Dodson et al 1991Dodson et al , 2007, restricting their potential to examine finer scale reproductive units, such as between habitat types in close geographic proximity. Whereas mtDNA tends to show historic patterns of reproductive isolation and colonization, microsatellites have a relatively fast mutation rate that makes them effective for detecting recent, fine-scale divergence (Selkoe and Toonen 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1) has several capelin populations: a number of small populations inhabiting fjords of the northern coast of Norway, and a large oceanic population with maturing individuals only migrating to the coast for spawning. Despite clear differences in life-history traits between coastal populations and the large oceanic population , no obvious genetic segregation between them has been detected (Mork and Friis-Sørensen 1983;Praebel et al 2008).…”
Section: Introductionmentioning
confidence: 99%